2023
DOI: 10.1021/acs.jmedchem.3c00213
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biaryl-Containing Aldo-Keto Reductase 1C3 (AKR1C3) Inhibitors for Reversing AKR1C3-Mediated Drug Resistance in Cancer Treatment

Abstract: Aldo-keto reductase 1C3 (AKR1C3) is correlated with tumor development and chemotherapy resistance. The catalytic activity of the enzyme has been recognized as one of the important factors in inducing anthracycline (ANT) resistance in cancer cells. Inhibition of AKR1C3 activity may provide a promising approach to restore the chemosensitivity of ANT-resistant cancers. Herein, a series of biaryl-containing AKR1C3 inhibitors has been developed. The best analogue S07-1066 selectively blocked AKR1C3-mediated reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…AKRs have been found to be upregulated in various cancers, including prostate cancer [ 6 ], hepatocellular carcinoma [ 7 ], breast cancer [ 8 ], non-small-cell lung cancer (NSCLC) [ 9 ] and SCLC [ 10 ]. Notably, AKR1C3 has been reported to be closely associated with the prognosis of different tumors and clinical drug resistance [ [11] , [12] , [13] , [14] ]. Previous study has shown that AKR1C3 promoted hepatocellular carcinoma cell proliferation and invasion through the IL6/STAT3 pathway by regulating NF-κB activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…AKRs have been found to be upregulated in various cancers, including prostate cancer [ 6 ], hepatocellular carcinoma [ 7 ], breast cancer [ 8 ], non-small-cell lung cancer (NSCLC) [ 9 ] and SCLC [ 10 ]. Notably, AKR1C3 has been reported to be closely associated with the prognosis of different tumors and clinical drug resistance [ [11] , [12] , [13] , [14] ]. Previous study has shown that AKR1C3 promoted hepatocellular carcinoma cell proliferation and invasion through the IL6/STAT3 pathway by regulating NF-κB activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%